Persepsi Guru Terhadap Penerapan Problem Based Learning Dalam Meningkatkan Kemampuan Siswa Dalam Berpikir Pada Kelas V SD - Mai Sri Lena; Hana Shilfia Iraqi; Asni Khoiriyah Nst; Hatika Prastiwina Hrp (CV. Aksara Global, 2023)
This article discusses the teacher's perception of Problem Based Learning to improve students' thinking skills. Critical thinking is something that every individual has in developing abilities. This model can be applied to increase student excellence in thinking to find a way out of a problem through direct experience and student knowledge. Problem Based Learning is a learning model that is given based on problems, where students are given a problem and asked to solve the problem critically. Researchers use descriptive qualitative because the information collected is in the form of verbal. Samples were taken from fifth grade elementary school teachers. This study states that students' ability to think in grade V elementary school increases by implementing PBL-based learning. Before using the PBL model in class V students, learning was too monotonous, lack of enthusiasm and passivity, and students also had difficulty understanding the material, less sharp dexterity of opinion, students' excess in thinking was less developed and less flexible. However, after using the PBL learning model, students' ability to think in class V is increasing in solving problems, students also become more responsive to the essence of the problem, students also become creative, active and critical and are increasingly able to find solutions to a problem, as well as students' thinking skills. growing and flexible.